CULTURE AS AN OBJECT OF ETHICAL GOVERNANCE IN AIDS PREVENTION. - Geary, AdamM (Cultural Studies)
This paper analyses AIDS-prevention therapeutics as ethical technologies of governance relative to the experience of culture. As a number of AIDS scholars have noted, the concept of 'culture' has been a powerful rubric for organizing evidence about HIV-transmission behaviours and their modification in prevention research and programming. Indeed, culture has been one of the most important concepts in AIDS-prevention knowledge through which danger is problematized, or organized as a specific problem that can be entered into strategies and techniques of governance and reform. This is to say that 'culture' functions in AIDS prevention as an object and target of government, toward which instruments, knowledges, and programmes are directed with the goal of transforming the behaviours and meanings said to put individuals at risk for HIV transmission. I argue that culture is experienced in prevention therapeutics as an element of the self toward which one is to form oneself as an active and ethical subject of one's own health. In AIDS-prevention pedagogies, individuals encounter 'culture' as a potentially dangerous element of the self, a force or drive within oneself that will overwhelm one's free and responsible decision-making capacity unless one forms a deliberate and authoritative relationship to it. These pedagogies cultivate in subjects techniques for constituting an authoritative relationship to culture, seeking to guarantee responsible behaviour and decision-making about HIV risk by constituting individuals as authoritative subjects of their cultures. As such, AIDS prevention is best understood as what Foucault called an 'ethical' governing strategy that forms individuals as active and responsible subjects of their cultures.